(untitled) (jornal of the libyan geographical society, 2009)
During the first half of the twentieth century, the number of independent countries in Africa did not exceed the fingers of one hand. By the end of the sixties, most of the countries of the continent had gained their political independence. By the beginning of the third millennium, the number of independent African countries had reached 53. With the decline of the colonial period and the rise of the sons of the continent to power, the African peoples looked forward to a new stage of security and stability, higher rates of economic growth, improved living standards, reduced levels of poverty and deprivation, and improved levels of education and health services. Half a century is enough time to judge the level of achievement. Is the level of achievement at the level of ambitions? What is the level of human development in Africa? What are the factors affecting those levels? A number of questions arise, and this paper attempts to answer some of them to the extent that data about the African continent is available, which lacks accuracy and credibility. Accordingly, this research paper has been divided into three main axes. The first axis is dedicated as a general introduction to human development and presents the most important measures used to measure it. The second axis is dedicated to analyzing the level and trends of human development, and it focuses on the basic dimensions of human development, which are a long and healthy life, renewed knowledge, and a decent standard of living. The third axis discusses the relationship of some factors to the levels of human development in the continent, including population growth, natural environment problems, conflicts and civil wars, political stability, and the level of economic performance. The paper concludes by drawing a number of conclusions about the level of human development in the continent, its trends, and the most prominent factors affecting it.